Peripheral Routes to Neurodegeneration: Passing Through the Blood–Brain Barrier - Giannoni, Patrizia; Claeysen, Sylvie; Noe, Francesco; Marchi, Nicola (Frontiers in Aging Neuroscience, 2020)
The existence of a bidirectional cross-talk between peripheral immune cells or organs and the central nervous system is well accepted. Here, we provide content supporting emerging mechanisms of neurodegeneration that are contingent on a pathological peripheral-brain interplay and cerebrovascular dysfunction or breakdown. We next examine the implication of peripheral auto-antibodies and the gut-brain axis in neurodegeneration. As accumulating evidence indicates that cerebrovascular dysfunction contributes or even anticipates neurodegeneration, we evaluate contemporary pharmacological strategies aimed at repairing or healing the cerebrovascular interface in disease conditions. Unorthodox multi-therapeutic approaches could accelerate an efficacious pre-clinical to clinical transition, ameliorating patient care.